2-(Phenylseleno)ethanesulfon-amide as a novel protecting group for aniline that can be deprotected by a radical reaction. Issue 23 (8th June 2016) - Kihara, Nobuhiro; Mitsuhashi, Yuji; Sato, Makoto; Hirose, Shun-ichi; Goudo, Erika; Uzawa, Yoshinori; Shirai, Natsumi; Hamamoto, Sari; Iwasaki, Ryo; Fujioka, Akane
Graphical abstract: Highlights: The radical reduction of 2-(phenylseleno)ethanesulfonamide (SeES amide) gives the corresponding amine. The SeES protection of amine can be accomplished with commercially available chemicals. The radical deprotection proceeds chemoselectively under neutral conditions. SeES amide, as a sulfonamide, is chemically stable. Abstract: Anilines were protected as 2-(phenylseleno)ethanesulfonanilide (SeES anilide) via sulfonylation by 2-chlorosulfonyl chloride followed by the conjugate addition of benzeneselenol. The SeES anilide was deprotected by radical reduction using tributyltin hydride in the presence of AIBN. The corresponding anilines were obtained in high yields when the hydride and AIBN were added to the system slowly. Since the radical reaction proceeds under neutral conditions, chemoselective deprotection of the SeES group was accomplished. The SeES anilide was stable under various conditions, including some severe conditions.